Analisis Strategi Customer Relationship Management untuk Meningkatkan Loyalitas Pelanggan dalam Pembelian Suku Cadang Pada PT Trakindo Utama Cabang BSD - Shelvina Putri Danisa; Muchsin Muthohar (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
Intense competition within the industrial sector drives companies to be more proactive in creating and continually designing strategies to maintain their position in the market. Companies that have customer relationship strategies can enhance customer loyalty, which in turn optimizes the long-term profitability of the company. Through this strategy, relationships with customers can be strengthened, and existing customers can be retained. The strategy is also implemented by one of the heavy equipment companies in Indonesia, namely PT Trakindo Utama Branch BSD, to effectively address customer complaints so that customers feel comfortable again despite their previous dissatisfaction with the services provided. This research aims to determine whether the implementation of customer relationship management strategies carried out by PT Trakindo Utama's BSD Branch can effectively enhance customer relationships, retain customers, and increase loyalty. The methodology used in this research is a qualitative approach, involving data collection techniques such as observation and interviews with employees of PT Trakindo Utama Branch BSD in the Sales division and the Parts Counter sub-division who have direct and intensive communication with customers, as well documentation. Therefore, the data obtained are accurate and based on sources within the company relevant to the research. Through observations and interviews, it can be seen that the customer relationship management strategies implemented by the company have been effective in improving and maintaining customer relationships and increasing customer loyalty by offering loyalty programs, such as excellent and solution-oriented services, providing incentives, annual contracts, membership rewards, and conducting evaluations based on customer assessments.